Peran Stakeholders dalam Konservasi Penyu Belimbing di Pantai Peneluran Jamursba Medi Kabupaten Tambrauw Provinsi Papua Barat - Yewen, Martha Yulita; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA, 2018)
The conservation potential of Leatherback Sea Turtle in Jamursba Medi Spawning Beach is for ecotourism attraction. This research was conducted at PeneluranJamursbaMedi Beach. This research was conducted to find out the potential of Leatherback Sea Turtle at JamursbaMediSpawningBeach as ecotourism attraction in Tambrauw Regency and also to find out the form of cooperation of Stakeholders in the area of Jamursba Medi Spawning Beach, Regency of Tambrauw, Province of West Papua. The type of data being used in this research was qualitative and quantitative with primary and secondary data source obtained through data sampling technique of depth interview observation, literature study with informant determination technique of purposive sampling and data analysis technique of descriptive qualitative. The result of research shows that in the area of Spawning Beach, Leatherback Sea Turtles have a potential to support tourism development in the form of natural, cultural and human. These three potencies are the assets to give contribution for tourism development and management of coastal park and has potential for ecotourism sector. So participation and active role of stakeholders namely Government, Population, and non-governmental organizations / WWF (World Wildlife Fund) is required for advancement and development in the area of Jamursba Medi Spawning Beach.   Key words: Potency, Ecotourism Conservation, Stakeholder.